2017
DOI: 10.1039/c7fd00006e
|View full text |Cite
|
Sign up to set email alerts
|

Upper tropospheric water vapour and its interaction with cirrus clouds as seen from IAGOS long-term routine in situ observations

Abstract: IAGOS (In-service Aircraft for a Global Observing System) performs long-term routine in situ observations of atmospheric chemical composition (O, CO, NO, NO, CO, CH), water vapour, aerosols, clouds, and temperature on a global scale by operating compact instruments on board of passenger aircraft. The unique characteristics of the IAGOS data set originate from the global scale sampling on air traffic routes with similar instrumentation such that the observations are truly comparable and well suited for atmosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 50 publications
3
23
0
Order By: Relevance
“…Thouret et al (2006) used a similar definition, but referenced to the dynamical tropopause at 2 PVU. A more detailed description of the methodology for determining the aircraft position relative to the thermal tropopause and for the vertical resolution of the data set is given by Berkes et al (2017). Since each data set from one single flight provides only a one-dimensional snapshot of the state of the atmosphere along the flight track, and each aircraft cruises at a slightly different pressure level, data are consolidated to 3-months season files, allowing the analysis of vertical distributions of atmospheric state parameters on a robust statistical basis.…”
Section: Data Coverage and Vertical Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thouret et al (2006) used a similar definition, but referenced to the dynamical tropopause at 2 PVU. A more detailed description of the methodology for determining the aircraft position relative to the thermal tropopause and for the vertical resolution of the data set is given by Berkes et al (2017). Since each data set from one single flight provides only a one-dimensional snapshot of the state of the atmosphere along the flight track, and each aircraft cruises at a slightly different pressure level, data are consolidated to 3-months season files, allowing the analysis of vertical distributions of atmospheric state parameters on a robust statistical basis.…”
Section: Data Coverage and Vertical Distributionmentioning
confidence: 99%
“…The transformation of both former research projects MOAZIC and CARIBIC into the current IAGOS Research Infrastructure took place in 2011. These regular flights on a global scale are unique in its quantity, continuity, and quality of measurements of Ex-UTLS air masses and have provided detailed insights into the distribution of RH ice (Gierens et al, 1999;Spichtinger et al, 2002), the distribution and properties of 120 ISSR (Gierens and Spichtinger, 2000;Spichtinger and Leschner, 2016), their link to cirrus clouds Petzold et al, 2017), and the processes controlling the water vapour distribution (Zahn et al, 2014).…”
mentioning
confidence: 99%
“…In situ measurements have demonstrated that young contrails are characterized by a high number of particularly small ice crystals (e.g., Petzold et al, 2017;Schröder et al, 2000;Voigt et al, 2010). Single contrails have been observed to persist in ice-supersaturated regions for many hours (Gierens & Vazquez-Navarro, 2018;Haywood et al, 2009;Minnis et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, UTLS H 2 O is monitored by a large variety of techniques including remote-sensing instruments on satellites (e.g., Randel et al, 2001;Rosenlof et al, 2001) and on ground (e.g., Vérèmes et al, 2016), as well as in situ instruments on balloons (e.g., Dirksen et al, 2014;Hurst et al, 2011;Vömel et al, 2002), research aircraft (e.g. von Hobe et al, 2013;Vaughan et al, 2008), and passenger aircraft (e.g., Petzold et al, 2017). Space-borne measurements provide global coverage and multiannual data sets; however, they are limited by low vertical resolution (typically 1-4 km) in the UTLS (e.g., Hegglin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%